2019
DOI: 10.3390/ijerph16234710
|View full text |Cite
|
Sign up to set email alerts
|

Results from Lithuania’s 2018 Report Card on Physical Activity for Children and Youth

Abstract: The Global Matrix 3.0 “Report Card” assessment of physical activity was developed to achieve a better understanding of the global variability in child and youth physical activity. Lithuania joined the Global Matrix 3.0. The aim of this article is to summarize the results of the first Lithuanian Report Card, which included 10 indicators, as representative of individual behaviors, sources, and settings of influence indicators, and a health-related characteristic. The grades for each indicator were based on the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
(93 reference statements)
1
4
0
Order By: Relevance
“…The facts from this part of the study indicated that only one-quarter of subjects were active in the sports clubs and that almost half of the parents think that the children are not safe when they are playing in the neighbourhood. That is in parallel with results for the same indicators in Chile ( 28 ), but rather worse than the results in Lithuania and Germany ( 14 , 27 ).…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…The facts from this part of the study indicated that only one-quarter of subjects were active in the sports clubs and that almost half of the parents think that the children are not safe when they are playing in the neighbourhood. That is in parallel with results for the same indicators in Chile ( 28 ), but rather worse than the results in Lithuania and Germany ( 14 , 27 ).…”
Section: Discussionsupporting
confidence: 61%
“…It is interesting to note that there is a general opinion that cities in Montenegro do not have enough bikeways and that traffic is not safe enough for cyclists ( 13 ). The low use of walking or bicycling could be related to the lack of pedestrian and bicycle infrastructure, as well as the actual or perceived dangers of walking and cycling ( 14 ). Of course, this does not necessarily mean that the number of children walking or cycling to school is related to the development level of a country ( 14 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Less than half of all Report Card studies involved government o cials (44,7%). However, the level of government involvement differed: While government o cials were part of the Research Work Group in some countries (52,53), other countries involved representatives of their government in single stages of the process such as data collection (54) or grade assignment (55). The approaches applied in the Report Card studies were classi ed as being purely or mainly research-driven or -if government representatives were part of the respective Research Work Groups -as co-productive.…”
Section: Overview Of Included Studiesmentioning
confidence: 99%
“…In studies examining the knowledge levels of physical education teachers and teacher candidates on health-related physical fitness, it was stated that health-related physical fitness knowledge level was insufficient Santiago et al, 2016;Yılmaz, 2019). However, studies have also reported that students' health-related physical activity knowledge is insufficient or inaccurate and that children's levels of physical activity are alarmingly low in many countries around the world (Aubert et al, 2018;Grasten et al, 2014;Keating et al, 2009;Placek et al, 2001;Sukys et al, 2019;Tremblay et al, 2014;Wilkie et al, 2016). Yılmaz and Hünük (2018) observed in their study that students with a high level of health-related physical fitness knowledge did not acquire this knowledge from physical education teachers.…”
mentioning
confidence: 95%